Test Anxiety Among Special Education Students at the University of Dohuk, Iraq: Prevalence, Predictors, and Intervention Implications - Arezi, Anfal Abdulhafidh Zainal; Arezi, Musaab Abdulhafidh Zainal (Jurnal Theologia, 2025)
Test anxiety remains a persistent and alarming phenomenon among university students, particularly in high-stakes academic environments. This study investigates the prevalence and determinants of test anxiety among special education students at the University of Dohuk, Iraq—a population often overlooked in regional educational research. Employing a quantitative cross-sectional design, data were gathered from 60 stratified participants using the Al-Ghadi Exam Anxiety Scale, covering cognitive, emotional, behavioral, and physiological dimensions. Results revealed significantly above-average levels of test anxiety (mean = 91.85), with no statistically significant differences based on gender or academic year. These findings challenge commonly held assumptions about demographic variation in anxiety and underscore the systemic, non-discriminatory nature of the issue. Contributing to both theory and practice, this study highlights that test anxiety in this context stems not only from personal psychological factors but also from structural rigidities in assessment and lack of institutional support. The study calls for culturally sensitive, curriculum-integrated interventions that address students' emotional well-being holistically. By identifying anxiety as a widespread and consistent educational barrier, especially in underrepresented regions like Kurdistan, this research advocates for evidence-based reforms to foster resilience, equity, and academic success in special education programs.